DINAMIKA MASYARAKAT KONSUMTIF BALI DALAM UPACARA AGAMA (GEBOKAN PERSPEKTIF EKONOMI) - I Made Sujana (Majalah Ilmiah Widyacakra, 2020)
ABSTRACTThere are 3 (three) economic issues regarding Production, distribution and consumption,and to overcome them must also be from that problem, namely how to produce more andbetter and diverse, and then from the production how to distribute it evenly and thoroughly toconsumers or society and further is how to consume to be more useful and beneficial tosociety. A good and right consumption if consumers can use it effectively means that it isright on target and is fully beneficial and this can improve economic growth and people'swelfare will be better, but if used consumptive or even excessive consumerism will be able toreduce economic growth. The basic framework of the teachings of Hinduism, especially inBali is divided into 3 (three) parts, namely Tattwa (philosophy), Susila (ethics) andCeremony (yadnya) all are integrated and related to one another. Tattwa means "that" whosedeeper meaning is "truth and belief" about God, Susila which means the basis of moral orgood behavior or actions, the third is the Hindu concept of ceremony which can beinterpreted by all movements around human life or activities in connecting with God, in aceremony requires a facility called upakara which in Bali is often called Banten which oneform is Gebogan or Pajengan whose contents consist of various products of the earth and ispresented sincerely before God. In the present era, the form and content of gebogan hasshifted which was originally filled from agricultural produce and arranged according toability, has now shifted to an even excessive lifestyle called consumerism and consumerism.Life, with the hope of the results of this study would certainly be known to be the cause andhow to overcome them.